SOME ASPECTS OF DEPRECIATION. - Samils, R. G. H. (The Accounting Review, 1927)
Abstract The position occupied by depreciation as a determinant of the profit or loss of an industrial concern is of equal importance to that of the inventory in the case of the mercantile firm, but while the public is awakening to the significance of correct inventory adjustments it appears still to embrace many delusions as to the nature and true significance of depreciation. The explanation of this lies possibly in the fact that depreciation, although a charge arising from the operation of tangible assets, has no reference to diminution of weight or volume and frequently no reference to any apparent physical deterioration. Confirmation of this view is to be found in the contrasting accuracy of the popular conception of depletion, for depletion is analogous to depreciation in all but one respect. Whatever its origin may be, this popular ignorance concerning depreciation is much to be regretted, for a balance sheet or any other accounting statement relative to an industrial concern is but half intelligible and may even be grossly misleading to any person incompetent to appreciate and criticize the policy of the directors with regard to depreciation.